Joint Relay Assignment and Power Allocation in Multi-Pairs Multi-Relays Two-Way Decode-and-Forward Network - Sijia Lou; Longxiang Yang (Dianxin kexue)
A joint power allocation and relay assignment algorithm for multi-pairs multi-relays two-way cooperative networks to improve system performance and decrease computation complexity was proposed. The proposed algorithm select best relays for each pair, then the selected relays use network coding to assist users exchanging signals. Meanwhile, this algorithm allocates power between all nodes participated in transmission under the total transmit power constraint.The expressions of bit error rate（BER）were derived in closed-form,and were verified by simulation. Numerical result shows that it has a performance improvement compared to the conventional equal power allocation scheme.